2005
DOI: 10.1080/10473289.2005.10464751
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality Modeling and Decisions for Ozone Reduction Strategies

Abstract: Despite the widespread application of photochemical air quality models (AQMs) in U.S. state implementation planning (SIP) for attainment of the ambient ozone standard, documentation for the reliability of projections has remained highly subjective. An "idealized" evaluation framework is proposed that provides a means for assessing reliability. Applied to 18 cases of regulatory modeling in the early 1990s in North America, a comparative review of these applications is reported. The intercomparisons suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Deviations from EPA-recommended modeled attainment test Roth et al (2005) extensively audited the overall modeling methodologies of SIPs for the earlier 1-hr ozone standard. Here, we instead focus on the extent to which SIP modeling approaches deviated from the standard EPA-recommended modeled attainment test (EPA, 2007b) in order to demonstrate attainment by the targeted date.…”
Section: State and Federal Measures In Sipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deviations from EPA-recommended modeled attainment test Roth et al (2005) extensively audited the overall modeling methodologies of SIPs for the earlier 1-hr ozone standard. Here, we instead focus on the extent to which SIP modeling approaches deviated from the standard EPA-recommended modeled attainment test (EPA, 2007b) in order to demonstrate attainment by the targeted date.…”
Section: State and Federal Measures In Sipsmentioning
confidence: 99%
“…Roth et al (2005) audited the modeling approaches of ozone SIPs and other regulatory modeling efforts in North America from the early 1990s, and found that the majority of cases lacked sufficient performance evaluation and corroborating analyses. Fine and Owen (2005) reviewed the attainment planning process in the San Joaquin Valley and highlighted specific shortcomings regarding modeling and public participation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, scenarios may represent emission levels under control strategies [12], or under projected climate change [13,14]. Other studies consider hypothetical percentage changes in emissions by species, source sector, or source region [15].…”
Section: Brute-force Methodsmentioning
confidence: 99%
“…"Attainment demonstrations" conducted to attain a previous air quality standard are rarely re-evaluated to determine why attainment was not achieved on the specified schedule. 40,41 The 40th annual A&WMA Critical Review 42,43 provides a conceptual framework for multipollutant air quality management and assessment of accountability. The review summarizes and elaborates on an extensive NARSTO 44 integrated assessment 45 of the same topic.…”
mentioning
confidence: 99%